Short‐Term, High‐Dose Fish Oil Supplementation Increases the Production of Omega‐3 Fatty Acid–Derived Mediators in Patients With Peripheral Artery Disease (the OMEGA‐PAD I Trial). Issue 8 (August 2015) - Grenon, S. Marlene; Owens, Christopher D.; Nosova, Emily V.; Hughes‐Fulford, Millie; Alley, Hugh F.; Chong, Karen; Perez, Sandra; Yen, Priscilla K.; Boscardin, John; Hellmann, Jason; Spite, Matthew; Conte, Michael S.
Abstract : Background: Patients with peripheral artery disease (PAD) experience significant morbidity and mortality. The OMEGA‐PAD I Trial, a randomized, double‐blinded, placebo‐controlled trial, addressed the hypothesis that short‐duration, high‐dose n‐3 polyunsaturated fatty acids (n‐3 PUFA) oral supplementation improves endothelial function and inflammation in PAD. Methods and Results: Eighty patients with stable claudication received 4.4 g of fish oil or placebo for 1 month. The primary end point was endothelial function as measured by brachial artery flow‐mediated vasodilation. Secondary end points included biomarkers of inflammation, n‐3 polyunsaturated fatty acids metabolome changes, lipid profile, and walking impairment questionnaires. Although there was a significant increase in FMD in the fish oil group following treatment (0.7±1.8% increase from baseline, P =0.04), this response was not different then the placebo group (0.6±2.5% increase from baseline, P =0.18; between‐group P =0.86) leading to a negative finding for the primary endpoint. There was, however, a significant reduction in triglycerides (fish oil: −34±46 mg/dL, P <0.001; placebo −10±43 mg/dL, P =0.20; between‐group differential P ‐value: 0.02), and an increase in the omega‐3 index of 4±1% ( P <0.001) in the fish oil group (placebo 0.1±0.9%, P =0.49; between‐group P <0.0001). We observed a significant increase in the production of pathway markers of specialized pro‐resolving mediators generated from n‐3 polyunsaturated fatty acids in the fish oil group. Conclusions: High‐dose, short‐duration fish oil supplementation did not lead to a different response in the primary end point of endothelial function between the treatment and placebo group, but improved serum triglycerides and increased the production of downstream n‐3 polyunsaturated fatty acids–derived products and mediators in patients with PAD. Clinical Trial Registration: URL:https://www.clinicaltrials.gov/ . Unique identifier: NCT01310270.